RICE and CCAFS contributed to restore a sustainable agri-food system in Vietnam through restructuring of the rice sector - CGIAR Research Program on Rice (2019)
By 2019, a few years after its issuance, the restructuring strategy has resulted in some positive impacts. Rice production started to develop in a more sustainable way with increasing proportion of fragrant and specialty rice. The large-scale rice fields model is expanding and adoption of improved practices is higher. Rice production also shows higher efficiency thanks to the rearrangement of cropping calendar to reduce risks of natural disasters such as floods and salt intrusion.